The Implementation of Prayer Value Education within Fisherman Families in Sukaraja Subdistrict, Bandar Lampung City - Rahul Abrian Djano; Umi Hijriyah; Era Octafiona (FKIP - Universitas Riau, 2026)
Prayer value education within fisherman families faces distinctive challenges due to economic pressure, irregular working schedules, and limited parental presence. These conditions significantly affect the consistency of children’s religious guidance, particularly in maintaining regular prayer practices during adolescence. This study aims to understand the implementation of prayer value education within fisherman families in Sukaraja Subdistrict, Bandar Lampung City, based on the lived experiences of parents and children. The research employed a qualitative approach using a phenomenological method. Data were collected through in depth interviews, observations, and documentation involving parents, children, and religious educators within the coastal community. The findings reveal that prayer education is primarily implemented through habituation, parental modeling, and direct supervision. However, these practices encounter structural limitations arising from economic demands, prolonged paternal absence due to fishing activities, and limited opportunities for reflective religious dialogue within the family. In response to these constraints, fisherman families develop a collaborative model of prayer supervision by involving Islamic learning centers (TPA) and schools as part of a broader religious education ecosystem. This study concludes that prayer value education in fisherman families is highly contextual and requires strengthened collaboration across educational environments to ensure the continuity and internalization of prayer values among children.